Pain management during a bromelain-based selective enzymatic debridement in paediatric and adult burn patients. Issue 3 (May 2022) - Claes, Karel E.Y.; Amar, Sarah; Hoeksema, Henk; Kornhaber, Rachel; de Jong, Alette; Monstrey, Stan; Haik, Josef; Biros, Erik; Harats, Moti
Highlights: Pain during eschar removal impedes procedures outside an operating theatre. Regional anaesthesia can be safely performed in paediatric and adult patients. Regional anaesthesia for burn wounds on one upper or one or two lower limbs. Both upper limbs should be debrided under regional anaesthesia on separate days. Abstract: Background: Pain associated with surgical or enzymatic burn wound debridement prevents many burn centres from working outside an operating theatre, creating a burden. Alternatives for general anaesthesia to manage pain in burn patients treated with enzymatic debridements, such as regional anaesthesia, have not been studied in detail. This study explores the different possibilities for pain management during a bedside NexoBrid™ procedure. Material and methods: We performed a single-centre retrospective study that included 82 paediatric, adolescent, and adult patients with deep dermal and full-thickness burns treated bedside with NexoBrid™ under regional or general anaesthesia. Outcome measures were pain during the NexoBrid™ procedure, the safety of the anaesthesia and the NexoBrid™ procedure, logistics of the bedside NexoBrid™ procedure, and time to wound closure. Results: Forty-three patients in the adult group (43/67, 64%) only presented with burn wounds on one upper or the one or two lower extremities. In 29 of them (29/43, 67%), a NexoBrid™ procedure was performed under regional anaesthesia, which resulted in low pain levels without any adverse events. All seven patients in the paediatric group, where only one upper or one or two lower limbs were involved (7/15, 47%), underwent a NexoBrid™ procedure performed under regional anaesthesia where no adverse events were reported. In these children, the use of regional anaesthesia was associated with a significant decrease in time to wound closure (average treatment effect on the treated = −22.5 days, p = 0.021). Conclusion: This study highlights that regional anaesthesia administered at the bedside should be the method of choice for pain management during NexoBrid™ procedures because often, it can be adequately and safely performed in all age groups. This approach will reduce the burden on operating theatres. A flow chart has been developed to guide pain management during a NexoBrid™ procedure.